Interactive AR Book Learning Media for Introducing Animal Types Based on Augmented Reality for Early Childhood - Farhan Fadhel Muhammad; Saiba Anjeli; Yuke Try Hafsani; Yoyon Efendi; Nurul Utami (Prosiding Seminar Nasional Ilmu Komputer, Sosial Sains, Teknik dan Multi-Disiplin Ilmu, 2026)
Augmented Reality (AR) is a technology that can display two-dimensional (2D) and three-dimensional (3D) virtual objects in real time through smartphone screens or other digital devices. In its application, AR technology utilizes markers in the form of certain images or images to display 3D objects that have been designed on the system. The implementation of Augmented Reality is currently widely used in various fields, one of which is in the field of education as an interactive learning medium for early childhood. The problem that is often found in the learning process is the use of learning media that is still conventional so that children easily feel bored and less interested when getting to know the type of animal. This research aims to design an interactive learning media AR Book to recognize animal types based on Augmented Reality in early childhood using Assemblr Studio. The research method used is Research and Development (R&D) with the ADDIE development model which consists of the analysis, design, development, implementation, and evaluation stages. The types of animals used include land, sea, and air animals that are displayed in the form of three-dimensional objects (3D) through the process of scanning markers using a smartphone. Learning media is also equipped with information on animal characteristics so that it helps children understand the material more interestingly and interactively. Research results show that Augmented Reality-based AR Book learning media can be used well as a learning tool and help increase early childhood learning interest in recognizing animal species.